Crude Turmeric Extract Improves the Suppressive Effects of Lactobacillus rhamnosus GG on Allergic Inflammation in a Murine Model of House Dust Mite-Induced Asthma - Ghiamati Yazdi, Fariba; Zakeri, Amin; Ark, Ingrid van; Leusink-Muis, Thea; Braber, Saskia; Soleimanian-Zad, Sabihe; Folkerts, Gert (Frontiers in Immunology, 2020)
There is a strong correlation between dysregulation of the gastrointestinal microbiota and development of allergic diseases. The most prevalent therapies for relieving asthma symptoms are associated with serious side effects, and therefore novel approaches are needed. Our objective was to elucidate whether oral administration of Lactobacillus rhamnosus GG (LGG) as a probiotic or turmeric powder (TP) as a prebiotic or both as a synbiotic mitigate allergic inflammation including lung function, airway inﬂammatory cell inﬁltration, Th2 cytokines/chemokine in a murine model of house dust mite (HDM)-induced asthma. BALB/c mice were intranasally sensitized and challenged with HDM received TP (20mg/Kg mouse), or/and LGG (105 cfu/ml or 107 cfu/ml), or both orally. Interestingly, the synbiotic intervention (HDM-TP-LGG E7) specifically could hinder the airway hyperresponsiveness in response to methacholine. Besides, our synbiotic, TP, and LGG strongly down-regulated eosinophilia, IL-5, CCL17, IL-13. In terms of T cell response, our flow cytometry results showed the reduction of CD4+ Th2 cells and CD4+ Th17 population in the splenocytes of treatment groups compared to control. Our synbiotic group not only elevated CD25+Foxp3+Treg frequency compared to asthmatic group, but also increased Treg cells compared to probiotic group. The synbiotic also indicated the superior effect in suppressing Th2 cells compared to probiotic. Although, TP and LGG alone display suppressive effects, we showed the combination therapy consisting of TP and LGG (synbiotic) is more effective than either of the treatments alone. The results of this study indicate that this novel synbiotic, might be considered as a potential food-based drug for translational medicine and can possibly be used along with corticosteroid treatment.